Evaluasi Ergonomis Alat Angkut Cangkang Buah Sawit Berdasarkan Konsep Enase - Nofirza Nofirza; Supardi Supardi (UIN Sultan Syarif Kasim Riau, 2012)
This research was the continuation of the earlier research which conducted to evaluate the design of palm fruit shells material handling using ENASE (Efisien “Efficient”, Nyaman “comfort”, Aman “Safe”, Sehat “Healthy”, Efektif “Effective”) concept. The data collected before and after the design processed for the standard time, heart beat rate, operator performance, and operator opinion from the questioners. The result showed the material handling designed made the system better than before. The Efficiency was showed by minimizing the working time (52,16%) and operator (50%). The Comfort gained by operator opinion that the handle is easy and comfort during the task. The Safety resulted from the using of wheel and tub which was appropriate with the worker and the conveyor. The Health was obtained from the reduce pain and suspended the fatigue from appears. While the Effective was accomplished from the standard output increasing (238%) which could sustain the productivity.Keywords: effective, efficient, ENASE, material handling, cangkang buah sawit